Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Photothermal-responsive Au nanorod-silica nanocomposite with on-demand curcumin release for sequential therapy of biofilm infections - Wenhui Jiang; Shunlan Luo; Kehan Du; Kai Yuan; Yuanhua Cong; Xiaoping Zeng; Dawei Wang; Hongyang Zhao; Huinan Suo; Liu Yang; Xiaowen Ou; Hao Jiang; et al. (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Carbapenem resistant Campylobacter jejuni bacteremia in a Bruton’s X-linked agammaglobulinemia patient - Ran Zhuo; Ramee L. Younes; Kevin Ward; Shangxin Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Immunocompromised patients are prone to recurrent Campylobacter infections. We report a case of recurrent multi-drug resistant Campylobactor jejuni bloodstream infections in a Bruton’s X-linked agammaglobulinemia patient with prolonged ertapenem treatment. The isolate from the fifth recurrence developed carbapenem resistance, which is associated with mutations in a porin gene porA , and promoter changes and duplication of chromosomal bla OXA-61 gene. Combination therapy using cefepime and doxycycline (later switched to moxifloxacin) cleared the infection.

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)